The Italian School at the Time of COVID-19-Implications for Students at the Personal and Didactic Level - Bogdan Stańkowski (Ignatianum University Press, 2021)
The author takes up the problem of education in Italy in the time of COVID-19. The objective of this article is to understand the impact of COVID-19 on the progress of school and the lives of children and adolescents. To pursue this cognitive objective, the author conducted an analysis of the relevant literature published between February 2020 and January 2021, mainly in Italian. The author has also formulated three research questions that will help investigate the above problem. The article is written with the help of the analytical method and takes into consideration the literature on the subject dedicated to children and adolescents. The analysis of the literature allowed the author to formulate final conclusions, which were developed in close correlation with the accepted research questions.